The theology of Islamic moderation education in Singkawang, Indonesia: The city of tolerance - Lailial Muhtifah (AOSIS, 2021)
This article explores the trends in the implementation of Islamic moderation through aqidah and sharia in Singkawang, as it is considered the most tolerant city in Indonesia based on a research report published in 2019. Using grounded research analysis, the authors found three structured patterns: implementation strategies (as related to vision, mission, position, programme and impact), implementation processes (as related to main actors, levels of success and obstacles) and implementation patterns. This study shows that these strategies and methods, implemented through a flexible, straightforward and easy-to-implement model are relevant to the fundamental values of Islamic education and offer a means of forming a complete and comprehensive network. These implementation patterns encourage religious communities to develop and maintain healthy social relationships. Hopefully, such implementation patterns can be imitated and modified by policyholders to realise Islam rahmatanlil ‘alamin [as a blessing for all].